Law of negligence with regard to the action of professional man / Mawar Ahmad Anuar - Ahmad Anuar, Mawar (Faculty of Law, 1987)
"Negligence" may signify full direct intention to one's conduct and its consequences 1, in which case it is a form of' the recklessness described above. More usually, however, it signifies direct intention by the defendant a simple example being the motorist who falls asleep at the wheel. It may be that the word should be used only in the latter Sense 2 but a defendant clearly cannot escape liability because he adverted to the risk if the case is one where even inadvertence would saddle him with liability. An illustration of full intention is VAUGEAN MENLOVE 3 where the defendant had been warned that his haystack was likely to overheat and to take fire, which might spread to the land of his neighbour. He said he would chance it 4, and he was held liable for the damage which occured when the stack actually took fire.